2013
DOI: 10.1111/1462-2920.12066
|View full text |Cite
|
Sign up to set email alerts
|

Genes expressed by the biological control bacterium Pseudomonas protegensPf‐5 on seed surfaces under the control of the global regulators GacA and RpoS

Abstract: Gene expression profiles of the biological control strain Pseudomonas protegens Pf-5 inhabiting pea seed surfaces were revealed using a whole-genome oligonucleotide microarray. We identified genes expressed by Pf-5 under the control of two global regulators (GacA and RpoS) known to influence biological control and secondary metabolism. Transcript levels of 897 genes, including many with unknown functions as well as those for biofilm formation, cyclic diguanylate (c-di-GMP) signalling, iron homeostasis and seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 127 publications
(215 reference statements)
13
65
0
Order By: Relevance
“…The wild-type subpopulation may dominate in other conditions, such as in the presence of competitors when GacS-GacA is needed to optimize fitness. Given the known role of GacS-GacA in controlling diverse cellular traits, including motility, biofilm formation, and secondary metabolism (15,16,20), spontaneous mutation of gacS or gacA provides a mechanism to regulate bacterial adaption at both cellular and population levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The wild-type subpopulation may dominate in other conditions, such as in the presence of competitors when GacS-GacA is needed to optimize fitness. Given the known role of GacS-GacA in controlling diverse cellular traits, including motility, biofilm formation, and secondary metabolism (15,16,20), spontaneous mutation of gacS or gacA provides a mechanism to regulate bacterial adaption at both cellular and population levels.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, different GacS-GacA-regulated phenotypes are likely to influence the relative fitness of Gac Ϫ mutants versus wild type in different conditions. For example, the motility of strain Pf-5 is influenced by the GacS-GacA system (16), and the predominance of Gac Ϫ mutants at the advancing edge of swarming colonies of P. protegens Pf-5 has been attributed to their hyperflagellation (17). Biofilm formation is also influenced by the GacS-GacA system (16), and Driscoll et al (23) reported evidence for a mutualism between Gac Ϫ mutant and wild-type cells of P. chlororaphis 30-84 in laboratory biofilms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, A. aculeatus Asp-4 up-regulated numerous genes and proteins involved in mitigation of environmental stress and dissolution of sclerotial compounds during colonization and degradation of sclerotia of S. sclerotiorum [81]. Omic studies of other biological control interactions revealed equally complex gene and/or protein expression profiles by biological control agents during interactions with pathogens or the environment [82][83][84]. In turn, soils and plant surfaces, where biological control agents are expected to effect disease control, are highly heterogeneous regarding compounds and conditions that impact expression of genes important to biological control; ultimately impacting expression of these genes and reliability and efficacy of disease control (reviewed in [80]).…”
Section: Use Of Plant-beneficial Microbes For Sustainable Crop Producmentioning
confidence: 99%